Urgensi Evaluasi dalam Komunikasi Dakwah Menurut Tafsir Ibnu Katsir QS. Al-Hasyr Ayat 18-19 - Diansah, Edo Ardo Arta; Erwin, Erwin; Prasongko, Wahyu Agung; Nurdin, Ali; Aisyah, Siti (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Evaluating communication in da’wah is a crucial step in achieving the desired or predetermined goals of da’wah. The focus and objective of this study are to understand and discuss the urgency of evaluation in da’wah communication according to Ibn Kathir’s interpretation of Quranic Al-Hasyr verses 18-19. The research method used in this study is a qualitative descriptive study with a library research approach. Data were collected using the Publish or Perish application with keywords “Urgency of Da’wah Evaluation” and “Dawah Evaluation” each with 10 scientific articles published in 2023 from Google Scholar, as well as additional data from books, scientific journals, documentation, and other relevant data. According to Ibn Kathir’s interpretation of Quranic Al-Hasyr verses 18-19, the study’s findings provide an understanding and meaning as an encouragement to evaluate all actions that have been performed. In the context of da’wah communication, preachers (da’i) are encouraged to evaluate all da’wah communication processes. Thus, da’i can perform improvements, evaluations, and enhancements in the Dawah communication process. The urgency of evaluation in da’wah communication includes several aspects, such as evaluating specific and organized da’wah goals, evaluating the suitability of da’wah messages with the needs of the audience, evaluating the quality of da’wah messages, evaluating the audience’s response or feedback, evaluating the audience’s involvement in the da’wah process, and evaluating the media used for da’wah communication.